The impact of COVID-19 on the level and structure of employment in European Union countries - Małgorzata Markowska; Andrzej Sokołowski (Comparative Economic Research. Central and Eastern Europe, 2023)
The paper proposes methods that can be used to evaluate the changes in one year of any measurable phenomenon based on how it performed in previous years. The following economic sections are considered: Agriculture, forestry and fishing/Industry/Construction/Wholesale and retail trade, transport, accommodation and food services/Information and communication/Financial and insurance activities/Real estate activities/Professional, scientific and technical activities, including administrative and support services/Public administration, defence, education, human health and social work/Arts, entertainment and recreation; other service activities; activities of household and extra-territorial organisations and bodies. The paper proposes a new method - called The Triple 2 Rule - to identify changes in employment time series. Trends and autoregressive models are estimated for the period 2008-2019, and 2020 forecasts are calculated. The difference between the forecasted and observed values for 2020 is treated as a measure of the impact of COVID-19. Dynamic cluster analysis based on 2008-2020 data is the second approach. The characteristics and changes in the composition of dynamic clusters give a picture of the impact of 2020. These changes can be considered to have been caused - at least partially - by the COVID-19 pandemic.
Keywords: C38; E24; F16; O52; 330; employment; COVID-19; European Union countries; dynamic cluster analysis; triple 2 rule